PENINGKATAN HASIL BELAJAR IPA MELALUI MODEL PEMBELAJARAN GROUP INVESTIGATION (GI) SISWA KELAS VI SDN 1 BAHARU UTARA KECAMATAN PULAULAUT UTARA KABUPATEN KOTABARU - Heriyadi Heriyadi (CENDEKIA: JURNAL ILMIAH PENDIDIKAN, 2021)
This research was motivated by the results of observations of science learning for sixth grade students at SDN 1 Baharu Utara which showed that their learning outcomes were still low. Therefore, this study aims to improve science learning outcomes through the Group Investigation (GI) learning model in grade 6 (six) students of SDN 1 Baharu Utara, Pulaulaut Utara subdistrict, Kotabaru Distric. The results showed that science learning outcomes increased after being given action through the application of the Group Investigation (GI) learning model. The average student learning outcomes in science increased from 52.50 to 63.75 in the first cycle and to 76.36 in the third cycle. Improvements were made in cycles II and III, namely at the grouping stage, which was originally each group consisting of 6 people into 3 people and the teacher's timing needs more attention. This is done so that students are more concentrated in small groups, teacher is easier to organize and guide students in groups. The third cycle, the science learning outcomes for students had reached 94.44% or 34 students were declared complete with scores above the KKM, the learning process was declared successful and stopped. Keywords: Science Learning Outcomes, Group Investigation (GI) Learning Model